Holding out the German army and operational command in 1917 - Cowan, Tony 1953- (Cambridge military histories, 2023)
This is a ground-breaking study of German operational command during a critical phase of the First World War from November 1916 to the eve of the third battle of Ypres. The situation faced by the German army on the Western Front in 1917 was very different from the one anticipated in pre-war doctrine and Holding Out examines how German commanders and staff officers adapted. Tony Cowan analyses key command tasks to get under the skin of the army's command culture, internal politics and battle management systems from co-ordinating the troops, matériel and different levels of command needed to fight a modern battle to continuously learning and applying lessons from the ever-changing Western Front. His detailed analysis of the German defeat of the 1917 Entente spring offensive sheds new light on how the army and Germany were able to hold out so long during the war against increasing odds.